2018
DOI: 10.1177/0960336017751466
|View full text |Cite
|
Sign up to set email alerts
|

Using blood near infrared spectra from steers to classify fat and meat samples with low or high levels of vaccenic acid

Abstract: Near infrared spectroscopy on steer blood was tested to discriminate between subcutaneous fat and longissimus thoracis samples with low or high levels of vaccenic acid. One day prior slaughter, blood samples from steers were harvested and near infrared spectra were collected on both whole blood and red blood cells. At slaughter, samples of subcutaneous fat and longissimus thoracis were collected and vaccenic acid content was analyzed by gas chromatography. Partial least squares discriminant analyses based on w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The use of GC for measuring fatty acid composition, however, still requires time and expertise and is incapable of predicting fatty acids in real time after blood sampling or in tissues at line speed in packing houses. To this end, some studies have shown promise for predicting concentrations of biohydrogenation intermediates in beef (Prieto et al, 2012, 2014) and whole blood (Prieto et al, 2018) using near infrared reflectance spectroscopy.…”
Section: Analysis Of Trans‐10 Intermediatesmentioning
confidence: 99%
“…The use of GC for measuring fatty acid composition, however, still requires time and expertise and is incapable of predicting fatty acids in real time after blood sampling or in tissues at line speed in packing houses. To this end, some studies have shown promise for predicting concentrations of biohydrogenation intermediates in beef (Prieto et al, 2012, 2014) and whole blood (Prieto et al, 2018) using near infrared reflectance spectroscopy.…”
Section: Analysis Of Trans‐10 Intermediatesmentioning
confidence: 99%